EVALUATE THE EFFECT OF CINNAMON ZEYLANICUM 0IL EXTRACT IN INHIBITION OF BACTERIA IN LABORATORY BISCUIT - Eshraq Gehad khudair; Sanaa A. AL sahib; Bahira M. AL-Timimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate effect of cinnamon zeylnicum oil extract in inhibition of bacteria in laboratory biscuit.revealed chemical research on cinnamon oil extract has the presence of alkaloids, glycosides, saponins, resins, coumarins, terpenes, flavonoids, and stimulants. Using GC-MS and FT-IR analysis, it was found that the hot water extract contains terpenes, glycosides, resins, saponins, and phenols, indicating the effectiveness of these beneficial components in cinnamon oil extract. Biscuits were manufactured in the laboratory and fortified with different concentrations (0.125%, 0.25%, 0.50%, and 0.75%) of C. Zeylanicum oil extract and stored for 10 days at room temperature. The results showed that 0.125% and 0.25% showed no inhibitory activity against bacterial counts, while those of 0.50% and 0.75% inhibited bacterial counts until the eighth day of storage. Regarding the sensory evaluation of the laboratory-manufactured biscuits fortified with cinnamon oil extract, treatment A5 (control) received the highest score of 6 for the texture property. In contrast, treatment A4 (0.75%) received the lowest score of 4.80. In the same property, for the smoothness attribute, treatment A2 (0.25%) received the highest score of 5.70, while treatment A4 (0.75%) received the lowest score of 4.10.